Digital Well-Being Work System Scale Development Using Content Validity and Exploratory Factor Analysis - Annisa Ciptagustia; Rofi Rofaida; Heny Hendrayati; Riskeu Faldesiani; Murni Zarina Razali; M. Ikhwan Maulana Haeruddin (Universitas Pendidikan Indonesia, 2025)
Digitalization intensifies connectivity demands and exposes early-career Generation Z banking employees to digital overload and boundary erosion, yet organizations still lack a system-level diagnostic to assess HR practices that protect digital well-being while sustaining performance. This study develops the Digital Well-Being Work System (DWWS) scale by translating HR-systems logic into six actionable domains and testing its initial psychometric properties. Item development combined domain specification and readability checks, followed by expert–user review (six raters) using the Content Validity Index (CVI). A main survey of 294 Generation Z banking employees in West Java was then analyzed using exploratory factor analysis (Principal Axis Factoring with Varimax rotation). Scale-level CVI showed excellent relevance and clarity (S-CVI/Ave = 0.965), with minor wording refinements to a small set of non-unanimous items before constructing testing. EFA supported a stable six-factor solution (KMO = 0.852; Bartlett’s p < .001) with moderate-to-strong loadings (≈0.555–0.751) across 24 retained items. The resulting DWWS offers a practical instrument to audit and improve organizational support for healthy digital work; future research should confirm the structure via CFA in an independent sample and test predictive validity across sectors.